2013
DOI: 10.1111/nep.12158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of levamisole supplementation on tetanus vaccination response rates in haemodialysis patients: A randomized double‐blind placebo‐controlled trial

Abstract: Levamisole as an immunomodulator drug has been demonstrated to improve the immune response to hepatitis B virus vaccination in haemodialysis patients. The aim of this randomized double-blind placebo-controlled trial was to evaluate the effect of levamisole supplementation on tetanus-diphtheria (Td) vaccine response rates in haemodialysis patients. Forty haemodialysis patients who had not received tetanus vaccination in a year before investigation and had unprotective anti-tetanus immunoglobulin G (IgG) levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…In the nine articles in this meta-analysis examining the effect of levamisole as an adjuvant on the HBV vaccine, individuals receiving a combination of the HBV vaccine and GM-CSF had a higher response rate (84.06%) compared with those who had the HBV vaccine alone (65.4%). These findings were in agreement with the results of many other studies in this area [5,19,20]. Some researchers have also recommended the application of levamisole to increase response rates to HBV due to its availability and low cost.…”
Section: Discussionsupporting
confidence: 91%
“…In the nine articles in this meta-analysis examining the effect of levamisole as an adjuvant on the HBV vaccine, individuals receiving a combination of the HBV vaccine and GM-CSF had a higher response rate (84.06%) compared with those who had the HBV vaccine alone (65.4%). These findings were in agreement with the results of many other studies in this area [5,19,20]. Some researchers have also recommended the application of levamisole to increase response rates to HBV due to its availability and low cost.…”
Section: Discussionsupporting
confidence: 91%
“…Based on these molecular mechanisms, several clinical studies have shown that when administered together with certain vaccines such as HBV and tetanus-diphtheria, levamisole can improve seroprotection in patients with ESRD on HD ( 78 79 80 81 ), whereas a few other studies did not show a beneficial effect ( 82 83 ). Moreover, a meta-analysis of four studies (328 patients) showed that the oral administration of levamisole at a dose of 80~120 mg for 4~6 months significantly increased seroconversion after HBV vaccination ( 75 ).…”
Section: Modulation Of DC Function In Patients With Esrdmentioning
confidence: 99%
“…Levamisole stimulates T lymphocytes and macrophages and improves cellular immunity [ 18 ]. Moreover, it has positive effects on the response rate of hemodialysis patients to tetanus vaccination [ 19 ].…”
Section: Discussionmentioning
confidence: 99%